Techniques [videorecording]. (Mount Kisco, N.Y. Center for Humanities, 1986)
Explains that the medium in which an artist works is more than a means of expression; it is part of expression itself. Describes various media, and discusses some famous works for each.
Keywords: Art -- Technique; Art -- Psychology; Art studies; Humanities